Takotsubo cardiomyopathy diagnosis and clinical management: A literature review - Oliveira, Maria Eduarda Hummel; Queiroz, Régia Nunes de; Filho, Humberto Borges Ribeiro; Rocha, Fernanda Rodrigues; Dias, Heike Felipe Rangel; Martins, Isabella Ribeiro; Pereira, Gabriela de Oliveira; Prado, Gabriel Corrêa do; Passos, Barbara Guarany; Amorim, Gabriel dos Santos; Borges, Victor Neves Alves; Ficagna, Camila do Amaral; et al. (Seven Editora, 2023)
This article is a systematic review of the literature on Takotsubo syndrome or cardiomyopathy, a rare heart condition that presents symptoms similar to those of angina or myocardial infarction but with significant changes in cardiac function that do not correspond to the typical coronary distribution of coronary artery disease. The review was performed by consulting the Pubmed, Scielo, and Medline databases. Studies were found that discuss the different diagnostic criteria, pathophysiology, and complications of Takotsubo syndrome, as well as the available treatments and challenges in the clinical management of this condition. The review highlights the importance of careful differential diagnosis to rule out other causes of similar symptoms and early treatment to avoid serious complications. However, there are still challenges in the clinical management of Takotsubo syndrome, including the lack of standardized guidelines and evidence regarding specific therapies. This review highlights the need for more research to improve understanding of the pathophysiology and develop more effective treatments for this rare condition. DOI:https://doi.org/10.56238/alookdevelopv1-185